Effect of intra-uterine administration of Lactobacillus bacteria on the steroid hormone profile in sub-clinical endometritis affected cows - H, MOHAMES SULAIMAN; R, SURESH KUMAR; T, SATHIAMOORTHY; K, PORTEEN; R, RAVIKUMAR; J, UMAMAGESWARI; K, KRISHNAKUMAR (The Indian Journal of Animal Sciences, 2024)
Infertility in bovines is a major cause of serious economic loss to the dairy farmers. A major reason for infertility is sub-clinical, retrograde uterine infections. Sub-clinical endometritis is endometrial inflammation without apparent clinical manifestation and usually without signs of infection. This condition may be due to uterine infections or an extended inflammatory period that exists after elimination of bacteria. At present, infertility treatment is mainly done with intrauterine antibacterials, antiseptics and less commonly by hormones. These days, the major problem faced by animal reproductive health workers is the multiple drug resistance pathogens because of the indiscriminate use of antibiotics.Therefore, a different approach for more effective treatment of subclinical endometritis with Lactobacilli and its role on the steroid hormone profile was studied. In the present study, estradiol-17 β values were lower in the sub-clinical endometritis  affected  cows.  Whereas,  intra-uterine administration of Lactobacillus bacteria caused significant increase in estradiol level in a cycle after treatment in cross- bred cows. Similarly, the circulating serum progesterone concentration was also found to be low in subclinical endometritis affected cows. These findings could be used for clinical and experimental interpretations. Further, the information on pulsatile release of gonadotropins and steroid hormones status, receptors and its control, the close relationship among hormones could be necessary for better understanding of the role of steroid hormones in sub-clinical uterine infections.